2019
DOI: 10.1136/bjsports-2018-100482
|View full text |Cite
|
Sign up to set email alerts
|

Developing common demographic data elements to include in future editions of the SCAT and Child SCAT: a modified international Delphi study

Abstract: BackgroundThe Sport Concussion Assessment Tool (SCAT) and Child SCAT are the ‘gold standard’ assessment tools for a suspected sport-related concussion (SRC). A number of ‘modifiers’ (eg, previous history of concussion) of a SRC have been identified. These may influence how the SCAT/Child SCAT results should be interpreted.ObjectivesTo achieve consensus, via an international panel of SRC experts, on which athlete/player and parent/caregiver demographic variables should be considered for inclusion in future edit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, patient characteristics of age, sex, and presence of ADD/ADHD, in addition to timing of clinical presentation and concussion history, did not demonstrate an association with recall performance. Previous research has identified patient characteristics associated with performance on standardized concussion evaluations, and the results of our study contribute to this growing area of literature [13,14,15,16,17,23].…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Furthermore, patient characteristics of age, sex, and presence of ADD/ADHD, in addition to timing of clinical presentation and concussion history, did not demonstrate an association with recall performance. Previous research has identified patient characteristics associated with performance on standardized concussion evaluations, and the results of our study contribute to this growing area of literature [13,14,15,16,17,23].…”
Section: Discussionmentioning
confidence: 53%
“…Consistent with existing literature, we hypothesized that specific demographic, injury, and clinical test characteristics, such as shorter time between injury and assessment, and presence of ADD/ADHD, would be associated with worse performance on immediate or delayed word recall testing. The performance associations identified in this study may contribute to ongoing considerations regarding the inclusion of specific data elements in future standardized concussion assessments [17].…”
Section: Accepted Manuscriptmentioning
confidence: 84%
See 1 more Smart Citation
“…3 Our study recruited 15 participants which is in the range of previous Delphi studies where 10-50 participants have been reported. 16,34,51,57,64,68 Importantly, based on the characteristics of our panel members including their clinical experience number of years using the KC concept and their highest professional degree (Table 1), its quality is considered high. This gives robustness and credibility to the results of the current study.…”
Section: Respondent Group Characteristicsmentioning
confidence: 99%
“…A priori consensus threshold of 70% was used in order to be more sensible and avoid missing possible items that might be of interest but it is lower than other similar Delphi studies. 56,57 There is currently no agreement in the literature about which is the "best" threshold (if any) to be used in Delphi studies. Importantly, different thresholds can produce different number of items retained at the end of the Delphi study.…”
Section: Research Strengths and Limitationsmentioning
confidence: 99%